IMPLEMENTASI BUSINESS DEVELOPMENT PADA UMKM BERBASIS DIGITAL (STARTUP) - Prasetya, Muhammad Dwiky Ilham; Pradana, Bayu Ilham (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study finds that (1) the company’s goal definition refers to its vision of the six-dimensional milestone of smart city, (2) the company’s start refers to the initiation of its business model, (3) the company’s idea phase starts from the board of directors and market demand, (4) the project plan consists of project-based business activities and mainstream business activities, (5) the business model is based on the Business Model Canvas, (6) the business plan was divided into two: for each product and for the overall business, (7) the development phase was conducted both in-house and through cooperation with other companies, (8) the prototyping was carried out by creating the Minimum Viable Products, (9) the test phase involves both internal and external parties, (10) the realization phase consists of Smart City Master Plan, Information and Communication Technology Blueprint, and Smart Branding Blueprint, (11) the lesson learned is marked by the decision-making queues and double positioning, (12) the communication and internal marketing was held by conducting weekly and biweekly meetings, (13) documentation refers to the company’s grand design, and (14) the company’s continuous improvement refers to the development of the next version.